2022
DOI: 10.1186/s41065-022-00241-0
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline promotes proliferation and migration of human HepG2 cells through activation of the PI3K/AKT/mTOR pathway

Abstract: Background Arecoline is a well-known risk factor for oral submucosal fibrosis and cancer. However, the mechanistic correlation between arecoline and hepatocellular cancer remains elusive. Here, we investigated the effect of arecoline on the proliferation and migration of human HepG2 hepatoma cells and its potential oncogenic mechanisms. Methods Bioinformatic technologies were used to identify the deferentially expressed miRNAs (DE-miRNAs) and hub t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…However, when TNF-α and IL-6 in epithelial cells are activated by arecoline, it inhibits cell movement but not proliferation (Figures 1 and 3). These findings suggest that low-dose arecoline may influence other factors associated with cell movement and proliferation, such as Wnt signaling [43] and microRNAs [44]. Even at low doses, accumulated arecoline still induces DNA damage in cells and triggers DNA repair processes [40].…”
Section: Discussionmentioning
confidence: 95%
“…However, when TNF-α and IL-6 in epithelial cells are activated by arecoline, it inhibits cell movement but not proliferation (Figures 1 and 3). These findings suggest that low-dose arecoline may influence other factors associated with cell movement and proliferation, such as Wnt signaling [43] and microRNAs [44]. Even at low doses, accumulated arecoline still induces DNA damage in cells and triggers DNA repair processes [40].…”
Section: Discussionmentioning
confidence: 95%
“…In hepatocytes, arecoline N -oxide exhibited higher cytotoxicity and caused more DNA damage than did arecoline [ 24 ]. A study conducted using human hepatoma cells revealed that low concentrations of arecoline induced cell proliferation and migration by activating the PI3K/Akt/mammalian target of rapamycin (mTOR) pathway [ 68 ]; unfortunately, these findings were not validated in studies using human, animal, or cellular models. Notably, an epidemiological study also indicated that BQ use was not associated with gastric or colorectal cancer [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al. [ 44 ] reported that miR-21-3p upregulated the expression of PI3K-AKT pathway factors, CDK1, CCND1 but decreased RAF1 expression in hepatocellular cancer cells. And Zhang et al.…”
Section: Discussionmentioning
confidence: 99%